2010
DOI: 10.1309/ajcp88wvrdrdfbas
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized-LDL/β2-Glycoprotein I Complexes Are Associated With Disease Severity and Increased Risk for Adverse Outcomes in Patients With Acute Coronary Syndromes

Abstract: Oxidized low-density lipoprotein (oxLDL)/beta(2)-glycoprotein I (beta2GPI) complexes have been implicated in atherogenesis. oxLDL/beta2GPI complexes were measured in 339 patients with suspected acute coronary syndromes. Approximately 68% had angiographically documented coronary artery disease (CAD) and significantly higher mean + or - SD levels of oxLDL/beta2GPI (3.75 + or - 6.31 U/mL) than patients with normal coronary arteries (2.21 + or - 3.03 U/mL; P = .0026). Patients with severe CAD had significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 38 publications
4
42
0
2
Order By: Relevance
“…An association between CAD and AMI with Other aPLs have been reported in previous studies (Shojaie and Jahromi, 2011;Jafarzadeh et al, 2011;Greco et al, 2010). …”
Section: Discussionsupporting
confidence: 53%
“…An association between CAD and AMI with Other aPLs have been reported in previous studies (Shojaie and Jahromi, 2011;Jafarzadeh et al, 2011;Greco et al, 2010). …”
Section: Discussionsupporting
confidence: 53%
“…Recent studies have shown that the measurement of oxLDL/β2GPI complexes in patients with cardiovascular diseases provides a novel marker for those patients prone to or at risk for coronary heart disease [3].…”
mentioning
confidence: 99%
“…Other aPLs have been reported to have association with CAD and AMI (Shojaie and Jahromi, 2011;Jafarzadeh et al, 2011;Greco et al, 2010;Urbanus et al, 2009;Jahromi et al, 2013b;2013c).…”
Section: Discussionmentioning
confidence: 99%